Odysseus’ characterizations through implicative meaning of EPIC: The Musical - Siti Munawarah; Maida Norahmi; Rezqan Noor Farid; Fadila Umi Khodijah; Windi Fitriyani (Linguistics Initiative, 2026)
This study aims to analyze the characterizations of Odysseus through implicature theory by Yule in EPIC: The Musical album. EPIC: The Musical is a musical song that tells Odysseus' journey as a legendary hero in the literary works of Homer. The researchers construct a pragmatics study using discourse analysis. The researchers analyze the 31 songs in the album to discover the implicature that portrays Odysseus' characters. In the finding, there were found 18 the characterizations that was divided into positive and negative traits. Based on the analysis, the most characterizations found in the song was ruthlessness. It showed the writer succeed to characterized Odysseus as a ruthless human who dared to defy God.